Regional Economic Outlook, October 2018, Western Hemisphere Department : An Uneven Recovery. (Regional Economic Outlook, 2018)
Amid escalating trade tensions, tighter financial conditions, and volatile commodity markets, economic recovery in Latin America and the Caribbean has both moderated and become more uneven.